The Influence of Clinical Leadership and Reporting Intensity on Patient Safety Culture: The Mediating Role of Blaming Culture in Hospitals - Ratna Puri; Natsir Nugroho; Duta Liana (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Background: Patient safety culture forms the cornerstone of safe and high-quality healthcare delivery. However, its implementation often encounters barriers, particularly the persistence of a blaming culture that discourages staff from reporting patient safety incidents. Clinical leadership and the intensity of incident reporting are believed to play a pivotal role in shaping and sustaining a positive patient safety culture.Objective: This study aims to examine the influence of clinical leadership and patient safety incident reporting intensity on patient safety culture, with blaming culture serving as an intervening variable at Sentra Medika Cikarang Hospital.Methods: A quantitative research approach with an explanatory design was applied. The study involved 147 nurses selected through stratified random sampling. Data were collected using structured questionnaires and analyzed using Structural Equation Modeling (SEM) with the Partial Least Squares (PLS) method to test the direct and indirect relationships among variables. Results: The findings revealed that both clinical leadership and incident reporting intensity significantly influence patient safety culture, both directly and indirectly, through the mediation of blaming culture. Strong clinical leadership and a high level of incident reporting were associated with a more positive patient safety culture, while a high blaming culture weakened this relationship. Conclusion: The study underscores the importance of fostering supportive clinical leadership and cultivating a non-punitive reporting environment to strengthen patient safety culture. Hospital management should focus on leadership development and the creation of open, blame-free communication systems to enhance safety outcomes.